Allelic variation in two distinct Pseudomonas syringae flagellin epitopes modulates the strength of plant immune responses but not bacterial motility - Clarke, Christopher R.; Chinchilla, Delphine; Hind, Sarah R.; Taguchi, Fumiko; Miki, Ryuji; Ichinose, Yuki; Martin, Gregory B.; Leman, Scotland; Felix, Georg; Vinatzer, Boris A. (The New phytologist, 2013)
The bacterial flagellin (FliC) epitopes flg22 and flgII-28 are microbe-associated molecular patterns (MAMPs). Although flg22 is recognized by many plant species via the pattern recognition receptor FLS2, neither the flgII-28 receptor nor the extent of flgII-28 recognition by different plant families is known. Here, we tested the significance of flgII-28 as a MAMP and the importance of allelic diversity in flg22 and flgII-28 in plant–pathogen interactions using purified peptides and a Pseudomonas syringae ΔfliC mutant complemented with different fliC alleles. The plant genotype and allelic diversity in flg22 and flgII-28 were found to significantly affect the plant immune response, but not bacterial motility. The recognition of flgII-28 is restricted to a number of solanaceous species. Although the flgII-28 peptide does not trigger any immune response in Arabidopsis, mutations in both flg22 and flgII-28 have FLS2-dependent effects on virulence. However, the expression of a tomato allele of FLS2 does not confer to Nicotiana benthamiana the ability to detect flgII-28, and tomato plants silenced for FLS2 are not altered in flgII-28 recognition. Therefore, MAMP diversification is an effective pathogen virulence strategy, and flgII-28 appears to be perceived by an as yet unidentified receptor in the Solanaceae, although it has an FLS2-dependent virulence effect in Arabidopsis.